Penerapan Just in Time (JIT) Sebagai Upaya Efisiensi Manajemen Persediaan Gudang Dalam Optimalisasi Profitabilitas PT IUB - Vanomy, Afrianti; Jeslin, Jeslin; Polii, Nanvy Jenix Dean; Sari, Amanda Novita; Putri, Jane Lovita; Winestia, Winestia; Candyce, Candyce; Alnandez, Leo; Raditya, I Made Guna; Iman, M. Febri Shahrul; Andy, Andy (Jurusan Akuntansi Politeknik Negeri Padang, 2025)
PT IUB is an e-commerce company that faces challenges in warehouse inventory management due to fluctuating market trends, resulting in stockpiling and decreased profitability. This study aims to evaluate the effectiveness of implementing the Just in Time (JIT) method in managing warehouse inventory and optimizing the company's profitability. The research uses a descriptive quantitative approach by comparing costs and efficiency between the company’s conventional policy and the JIT method. The analysis includes indicators such as order frequency, total inventory cost, and Manufacturing Cycle Efficiency (MCE). The results indicate that JIT implementation significantly reduces ordering and storage costs and increases net profit, particularly for shoe products. Moreover, process efficiency improves through workflow simplification. In conclusion, the JIT method has proven to have a positive impact on enhancing inventory management efficiency and the profitability of PT IUB.